Examining the Relationship Between Work Motivation and Job Satisfaction Among Nurses in Inpatient Care Units - Anggi Tri Octavelia; Fatma Indriani (Karya Kesehatan Siwalima, 2026)
Job satisfaction reflects the alignment between individuals’ expectations and the rewards provided by their work; therefore, it is closely associated with work motivation theory. This study aimed to examine the relationship between work motivation and job satisfaction among nurses working in the inpatient ward of Sundari General Hospital. A quantitative approach with a cross-sectional design was employed, involving 56 respondents selected through a total sampling technique, whereby all members of the population were included as the study sample. Data were collected using a structured questionnaire and analyzed using Spearman’s rank correlation test. The results indicated a statistically significant relationship between work motivation and job satisfaction (p = 0.010), with a positive correlation of moderate strength. These findings suggest that higher levels of work motivation are associated with higher levels of job satisfaction among inpatient nurses. In conclusion, increasing nurses’ work motivation may contribute to enhanced job satisfaction. Therefore, hospital management is encouraged to implement strategies aimed at improving nurses’ work motivation to further enhance their job satisfaction.